2016
DOI: 10.1016/j.drugalcdep.2016.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of comorbid PTSD in treatment-seeking alcohol dependent inpatients: Severity and personality trait differences

Abstract: Background Post-traumatic stress disorder (PTSD) is often comorbid with alcohol dependence (AD), but little is known about the characteristics of AD treatment-seeking inpatients with PTSD. We examined differences between treatment-seeking alcohol dependent inpatients with and without comorbid PTSD. We hypothesized that those with AD and PTSD would have higher levels of: (1) alcohol use and AD severity; (2) anxiety and mood disorders; (3) neuroticism. Methods Individuals (N=411, mean age = 41.7 ± 10.0 years) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 39 publications
2
15
1
Order By: Relevance
“…In this study, only male rats with a history of alcohol consumption showed stress-induced increases in startle reactivity after bobcat urine exposure. In agreement with these findings, previous studies have reported that individuals with comorbid PTSD and alcohol misuse exhibit more severe PTSD symptoms [54,55]. Startle reactivity was tested 6 days after the last drinking session (i.e., not during intoxication).…”
Section: Discussionsupporting
confidence: 75%
“…In this study, only male rats with a history of alcohol consumption showed stress-induced increases in startle reactivity after bobcat urine exposure. In agreement with these findings, previous studies have reported that individuals with comorbid PTSD and alcohol misuse exhibit more severe PTSD symptoms [54,55]. Startle reactivity was tested 6 days after the last drinking session (i.e., not during intoxication).…”
Section: Discussionsupporting
confidence: 75%
“…There is substantial research demonstrating that people with post‐traumatic stress disorder (PTSD) frequently have co‐occurring substance use disorders (SUD) and that they typically evidence greater impairment than individuals with either one or the other disorder . However, these investigations have taken different approaches when populating the groups, making comparisons across studies challenging.…”
Section: Introductionmentioning
confidence: 99%
“…We anticipated more individuals with life‐time PTSD/DUD would meet past‐year diagnostic criteria for one or more of the disorders comprising the comorbidity and would also evidence greater social and clinical impairment than those with life‐time PTSD/AUD . We also anticipated that the comorbid groups would evidence greater social and psychiatric impairment than their single disorder comparators .…”
Section: Introductionmentioning
confidence: 99%
“…Co‐occurring PTSD and AUD (PTSD–AUD) can have additive, interacting effects on mental and physical health and quality of life (QoL). Indeed, PTSD–AUD is associated with more severe symptoms, greater functional impairment, increased suicide risk, and greater treatment utilization than either disorder alone (Rojas, Bujarski, Babson, Dutton, & Feldner, ; Sells et al., ). Because PTSD and AUD share common mechanisms, particularly in terms of maintenance, integrated treatment is recommended (VA/DoD, 2010).…”
mentioning
confidence: 99%